High-stability sulfo polar metal halide perovskite crystal and preparation method and application thereof
By synthesizing sulfide polar metal halide perovskite crystals with the chemical formula (4-SP)4Pb3Br10·2H2O, the structural instability and ion migration problems of two-dimensional metal halide perovskite X-ray detectors were solved, efficient carrier separation and transport were achieved, and detection performance and stability were improved.
Patent Information
- Application Number
- CN202510922609.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-04
- Publication Date
- 2025-10-14
- Estimated Expiration
- 2045-07-04
AI Technical Summary
The existing two-dimensional metal halide perovskite X-ray detector material structure is unstable and ion migration is severe, resulting in detector instability and performance degradation, which is especially obvious when used under high electric fields. In addition, the development of heterojunction materials is complex.
Sulfur-substituted polar metal halide perovskite crystals with the chemical formula (4-SP)4Pb3Br10·2H2O were synthesized by the cooling crystallization method. By introducing 4-aminothiophenol to form NH···Br and SH···Br hydrogen bonds, the polarity and stability of the crystals were enhanced, and the slow cooling growth method was used to optimize the crystal structure.
It achieves efficient carrier separation and transmission under zero bias, improves X-ray detection performance and material stability, reduces dark current drift and baseline noise, and extends service life.
Smart Images

Figure CN120776453A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of artificial crystal materials in the field of functional crystal materials, and in particular relates to a highly stable sulfide polar metal halide perovskite crystal, a preparation method thereof, and uses thereof. Background Art
[0002] X-ray detection technology plays an indispensable role in medical testing, security inspections, and scientific research. Traditional X-ray detector materials are mainly based on silicon, α-Se, etc., which have weak X-ray absorption and severe attenuation, resulting in low detection performance, which greatly limits its development. In recent years, metal halide perovskites have shown great potential in the field of X-ray detection due to their strong X-ray absorption ability caused by the presence of heavy elements such as lead and halogens (bromine (Br), iodine (I)). Among them, two-dimensional perovskites have attracted great attention due to their diverse structures and strong designability. At present, X-ray detectors based on two-dimensional metal halide perovskites have made significant progress, but the instability of the detector caused by their unstable structure remains an obstacle to be overcome.
[0003] Currently, several effective approaches have been developed to improve material stability, such as enhancing the interactions between organic layers through halogen and hydroxyl substitution. These interactions can effectively promote carrier transport, thereby improving the material's X-ray detection performance. However, these materials still suffer from a large interlayer spacing, which is highly unfavorable for carrier transport. Furthermore, the organic components are arranged in a double layer between the layers, and the upper and lower layers are connected by weak van der Waals interactions, which significantly weakens the structural stability. Furthermore, the inevitable ion migration in perovskite materials remains a significant challenge. Halogen vacancy-induced ion migration is particularly pronounced when the materials operate continuously under high electric fields. Migrating ions accumulate at the electrode interface to form a space charge layer, causing a significant increase in dark current drift and baseline noise. Furthermore, under prolonged high external electric fields, the irreversible accumulation of migrating ions can lead to lattice distortion, further damaging the material structure. Therefore, inhibiting ion migration not only effectively improves the material's detection performance but is also a key factor in enhancing its stability and lifetime. Recently, a method for effectively suppressing ion migration is to enable the material to operate without an applied voltage, i.e., a self-driven detection mode. This detection mode requires the material to self-generate the built-in electric field required to separate and transport carriers. Currently, the materials that meet this condition are mainly polar materials and heterojunction materials. However, the complex development process of heterojunction materials has slowed their development in this field. Therefore, the development of new polar metal halide perovskites with both high performance and high stability, with the core goal of suppressing ion migration and promoting carrier transport efficiency, for the preparation of X-ray detection materials has important theoretical and practical value. Summary of the Invention
[0004] In response to the above technical problems, the present invention proposes a highly stable sulfide polar metal halide perovskite crystal, a preparation method thereof, and uses thereof.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] One of the purposes of the present invention is to provide a highly stable sulfide polar metal halide perovskite crystal, the chemical formula of which is (4-SP)4Pb3Br 10 2H2O, molecular formula is C 24 H 36 N4O2S4Pb3Br 10 ; Wherein, 4-SP represents 4-aminothiophenol. Crystal (4-SP)4Pb3Br was synthesized by cooling crystallization method. 10 2H2O, the chemical reaction formula is:
[0007] 4(4-SP)+3Pb(Ac)2·3H2O+10HBr→(4-SP)4Pb3Br 10 ·2H2O+6HAc+7H2O.
[0008] The invention achieves high stability and excellent X-ray detection performance through a specific chemical composition. The introduction of 4-aminothiophenol not only enhances the polarity of the crystal but also connects it to the inorganic framework via two hydrogen bonds: NH···Br and SH···Br, improving the stability of the structure.
[0009] Furthermore, the sulfide polar metal halide perovskite crystal belongs to the orthorhombic crystal system and the space group is Aea2.
[0010] In this study, the structural characteristics of the orthorhombic system and the Aea2 polar space group contribute to understanding the symmetry and arrangement of crystals, which have a significant impact on their physical properties, such as optical and electrical properties. In particular, the photovoltaics induced by the spontaneous polarization effect of this polar single crystal material enable efficient carrier separation and transport without an applied bias, thus enabling highly efficient self-driven X-ray detection.
[0011] Furthermore, the unit cell parameters of the sulfide polar metal halide perovskite crystal are: α=90°, β=90°, γ=90°, Z = 4, density is 2.842 g / cm 3 .
[0012] In the present invention, these parameters precisely define the structure of the crystal and help understand its physical and chemical properties. For example, a larger unit cell volume and a suitable density help improve the stability and X-ray absorption ability of the crystal.
[0013] A second object of the present invention is to provide a method for preparing highly stable sulfo-polar metal halide perovskite crystals, comprising the following steps: mixing 4-aminothiophenol and lead acetate trihydrate, then adding an aqueous HBr solution, heating and stirring until the solution becomes a colorless clear solution; and subjecting the obtained colorless clear solution to a crystallization post-treatment to obtain highly stable sulfo-polar metal halide perovskite crystals.
[0014] The method is simple and efficient, and can produce high-quality crystals. By controlling the reaction conditions, the growth of the crystals can be optimized, thereby improving their stability and performance.
[0015] Furthermore, the specific operation steps of the post-crystallization treatment include: placing the obtained colorless clear solution in a high-temperature oven at a temperature of 120°C while it is hot, and slowly cooling the solution to room temperature through a slow cooling growth method at a cooling rate of 1°C per day.
[0016] In the present invention, the natural cooling method is suitable for rapidly preparing microcrystals, while the slow cooling growth method can produce larger crystals suitable for different application scenarios. The slow cooling growth method can further improve the quality and stability of the crystals.
[0017] Furthermore, the molar ratio of the 4-aminothiophenol to lead acetate trihydrate is 1.5:1.
[0018] In the present invention, the molar ratio ensures that the reaction proceeds completely while optimizing the structure and performance of the crystal. An appropriate molar ratio can improve the stability and X-ray absorption capacity of the crystal.
[0019] Furthermore, the molar ratio of the lead acetate trihydrate to HBr in the HBr aqueous solution is 1:(20-35).
[0020] In the present invention, this molar ratio range ensures that the reaction proceeds fully while avoiding side reactions caused by excessive HBr. An appropriate molar ratio can improve the purity and quality of the crystals.
[0021] Furthermore, the mass fraction of the HBr aqueous solution is 48%.
[0022] In the present invention, the 48% HBr aqueous solution has a moderate concentration, which can ensure the smooth progress of the reaction while avoiding the corrosiveness and danger caused by excessively high concentration.
[0023] Furthermore, the heating temperature is 80-120°C.
[0024] In the present invention, this temperature range ensures efficient reaction while avoiding side reactions and damage to the crystal structure caused by excessively high temperatures. Appropriate temperature can improve the growth quality and stability of crystals.
[0025] A third object of the present invention is to provide a highly stable sulfide polar metal halide perovskite crystal for use in the preparation of X-ray detectors.
[0026] The crystal exhibits excellent performance in X-ray detection, such as high sensitivity, low detection limit, and high stability. These properties make it promising for broad applications in medical testing, security inspections, and scientific research.
[0027] Compared with the prior art, the present invention has the following advantages and technical effects:
[0028] This invention prepares a highly stable sulfide-substituted polar metal halide perovskite crystal. This crystal, when used in an X-ray detector, can achieve efficient and stable X-ray detection under both zero and high bias voltages. The X-ray response of this single crystal was tested using different X-ray doses. The crystal exhibited distinct photoresponse when exposed to different X-ray doses. These results indicate the potential application of this material as an X-ray detector. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The accompanying drawings, which constitute part of the present invention, are provided to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are provided to explain the present invention and do not constitute an undue limitation of the present invention. In the accompanying drawings:
[0030] Figure 1 (4-SP)4Pb3Br prepared in Example 2 of the present invention 10 Photograph of 2H2O crystals;
[0031] Figure 2 (4-SP)4Pb3Br prepared in Example 2 of the present invention 10 ·Structural stacking diagram of 2H2O crystal;
[0032] Figure 3 (4-SP)4Pb3Br prepared in Example 2 of the present invention 10 X-ray powder diffraction pattern of 2H2O crystals;
[0033] Figure 4 (4-SP)4Pb3Br prepared in Example 2 of the present invention 10 UV-visible absorption spectrum of 2H2O crystals;
[0034] Figure 5 (4-SP)4Pb3Br prepared in Example 2 of the present invention 10 Thermal stability decomposition curve of 2H2O crystal;
[0035] Figure 6 (4-SP)4Pb3Br prepared in Example 2 of the present invention 10 The nonlinear frequency-doubled signal intensity of 2H2O crystal;
[0036] Figure 7 (4-SP)4Pb3Br prepared in Example 2 of the present invention 10 X-ray detection sensitivity of 2H2O crystals;
[0037] Figure 8 (4-SP)4Pb3Br prepared in Example 2 of the present invention 10X-ray detection limit of 2H2O crystals;
[0038] Figure 9 (4-SP)4Pb3Br prepared in Example 2 of the present invention 10 Dark current drift value of 2H2O crystal;
[0039] Figure 10 (4-SP)4Pb3Br prepared in Example 2 of the present invention 10 Stability of 2H2O crystals tested under high X-ray doses;
[0040] Figure 11 (4-SP)4Pb3Br prepared in Example 2 of the present invention 10 Comparison of the initial detection sensitivity of the 2H2O crystal and its sensitivity two months later. DETAILED DESCRIPTION
[0041] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0042] It should be understood that the terms described herein are intended only to describe particular embodiments and are not intended to limit the present invention. In addition, for numerical ranges herein, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between any intermediate value within a stated value or stated range and any other stated value or intermediate value within the stated range is also encompassed by the present invention. The upper and lower limits of these smaller ranges may be independently included or excluded within the scope.
[0043] Unless otherwise indicated, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of any conflict with any incorporated document, the contents of this specification shall prevail.
[0044] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments described herein without departing from the scope or spirit of the invention. Other embodiments will be apparent to those skilled in the art from the description of the invention. The description and examples are intended to be illustrative only.
[0045] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0046] An embodiment of the present invention provides a method for preparing highly stable sulfo-polar metal halide perovskite crystals, comprising the following steps: mixing 4-aminothiophenol and lead acetate trihydrate, then adding an aqueous HBr solution, heating and stirring until the solution becomes a colorless clear solution; and performing a crystallization post-treatment on the obtained colorless clear solution to obtain highly stable sulfo-polar metal halide perovskite crystals.
[0047] In the following preferred embodiments of the present invention, the post-crystallization treatment comprises placing the resulting colorless, clear solution while still hot in a high-temperature oven at 120°C and slowly cooling the solution to room temperature via a slow cooling growth method at a rate of 1°C per day. This post-treatment method is required to produce single crystals larger than millimeters in size, which meet the requirements for preparing single-crystal X-ray detectors.
[0048] If the post-processing is carried out as follows: the obtained colorless clear solution is naturally cooled to room temperature to obtain colorless block-shaped microcrystals, which are then filtered and dried; the extremely small microcrystals obtained are mainly used to determine basic characterizations such as crystal structure and ultraviolet absorption, but cannot be used to prepare X-ray detection devices.
[0049] Method 2: The obtained colorless clear solution is placed in a high-temperature oven at 120°C while still hot, and the solution is slowly cooled to room temperature by a slow cooling growth method at a cooling rate of 1°C per day.
[0050] In the following preferred embodiments of the present invention, the molar ratio of 4-aminothiophenol to lead acetate trihydrate is 1.5:1.
[0051] In the following preferred embodiments of the present invention, the molar ratio of the lead acetate trihydrate to the HBr in the HBr aqueous solution is 1:(20-35). As an example, in the following embodiments of the present invention, the molar ratio of the lead acetate trihydrate to the HBr in the HBr aqueous solution is more preferably 1:26.
[0052] In the following preferred embodiments of the present invention, the mass fraction of the HBr aqueous solution is 48%.
[0053] In the following preferred embodiments of the present invention, the heating temperature is 80-120° C. As an example, in the following embodiments of the present invention, the heating temperature is more preferably 105° C.
[0054] The application of the highly stable sulfide polar metal halide perovskite crystal in the preparation of X-ray detectors. The results of X-ray single crystal diffraction show that the molecular formula of the compound is C 24H 36 N4O2S4Pb3Br 10 , the structural formula is (4-SP)4Pb3Br 10 ·2H2O. Wherein, 4-SP represents 4-aminothiophenol. At room temperature, (4-SP)4Pb3Br 10 2H2O crystals belong to the orthorhombic system, with space group Aea2. The unit cell parameters of the crystals are: α=90°, β=90°, γ=90°, Z = 4, density is 2.842 g / cm 3 .
[0055] Unless otherwise specified, the "room temperature" in the present invention refers to 25±2°C.
[0056] The raw materials used in the present invention are all purchased from the market.
[0057] The technical solution of the present invention is further illustrated by the following examples.
[0058] Example 1
[0059] A preparation method of a highly stable sulfo-polar metal halide perovskite crystal comprises the following steps: placing 4-aminothiophenol and lead acetate trihydrate in a beaker at a molar ratio of 1.5:1, then adding a 48% HBr aqueous solution to the beaker, wherein the molar ratio of the lead acetate trihydrate to the HBr aqueous solution is 1:26, heating to 105° C. and stirring until the solution becomes a colorless clear solution; naturally cooling the obtained colorless clear solution to room temperature to obtain colorless block-shaped microcrystals, filtering, and drying to obtain highly stable sulfo-polar metal halide perovskite crystals ((4-SP)4Pb3Br 10 ·2H2O).
[0060] Example 2
[0061] A method for preparing a highly stable sulfide polar metal halide perovskite crystal comprises the following steps: placing 4-aminothiophenol and lead acetate trihydrate in a beaker at a molar ratio of 1.5:1, then adding a 48% HBr aqueous solution to the beaker, wherein the molar ratio of HBr in the lead acetate trihydrate to the HBr aqueous solution is 1:26, heating to 105°C and stirring until the solution becomes a colorless clear solution; placing the obtained colorless clear solution while hot in a high-temperature oven at 120°C, and slowly cooling the solution to room temperature by a slow cooling growth method at a cooling rate of 1°C per day, thereby obtaining a crystal with a size of 5×3×2 mm. 3 Highly stable sulfide polar metal halide perovskite crystals ((4-SP)4Pb3Br 10·2H2O).
[0062] Figure 1 (4-SP)4Pb3Br prepared in Example 2 of the present invention 10 Photograph of 2H2O crystals.
[0063] The results of X-ray single crystal diffraction showed that the molecular formula of the compound is C 24 H 36 N4O2S4Pb3Br 10 , the structural formula is (4-SP)4Pb3Br 10 ·2H2O. Wherein, 4-SP represents 4-aminothiophenol. At room temperature, (4-SP)4Pb3Br 10 2H2O crystals belong to the orthorhombic system, with space group Aea2. The unit cell parameters of the crystals are: α=90°, β=90°, γ=90°, Z = 4, density is 2.842 g / cm 3 .
[0064] Figure 2 (4-SP)4Pb3Br prepared in Example 2 of the present invention 10 ·Structural stacking diagram of 2H2O crystal. Figure 2 It can be seen that (4-SP)4Pb3Br 10 2H2O has the following structure: (4-SP)4Pb3Br 10 The 4-aminothiophenol organic cations in the 2H2O are neatly arranged between the layers, forming a typical two-dimensional monolayer perovskite structure. Furthermore, 4-aminothiophenol is directly connected to the PbBr6 inorganic backbone via strong NH…Br and SH…Br hydrogen bonds formed at both ends of the molecule. This not only shortens the interlayer spacing, facilitating efficient carrier transport, but also eliminates van der Waals interactions between the organic components, resulting in greater structural stability.
[0065] The (4-SP)4Pb3Br prepared in Example 2 was analyzed by X-ray powder diffraction. 10 Phase purity of 2H2O crystals (such as Figure 3 The X-ray diffraction pattern obtained by structural simulation matches the experimentally measured results.
[0066] The (4-SP)4Pb3Br prepared in Example 2 was characterized by UV-visible absorption spectroscopy. 10 The optical absorption of 2H2O was analyzed, and the results were as follows Figure 4 shown. Figure 4Show (4-SP)4Pb3Br 10 The absorption cutoff edge of 2H2O is 386nm. According to the Tauc equation, the optical band gap of this compound can be deduced to be 3.19eV.
[0067] Figure 5 (4-SP)4Pb3Br prepared in Example 2 10 The thermal stability decomposition curve of 2H2O crystals shows that (4-SP)4Pb3Br 10 The decomposition temperature of 2H2O is 207℃.
[0068] The (4-SP)4Pb3Br prepared in Example 2 10 The nonlinear frequency doubling signal of 2H2O crystal is analyzed, and the results are as follows Figure 6 As shown, Figure 6 It shows that (4-SP)4Pb3Br 10 The nonlinear signal intensity of 2H2O is 1.1 times that of potassium dihydrogen phosphate (KDP).
[0069] Application Example 1
[0070] The (4-SP)4Pb3Br prepared in Example 2 10 ·2H2O crystals are used to construct single crystal X-ray detectors. The specific method is to select a single crystal X-ray detector with a volume of about 3×2×1mm. 3 A high-quality single crystal is placed on a glass sheet, and Ag electrodes are evenly applied on both ends of the crystal (along the polar axis: the crystallographic c-axis), and then led out with wires at both ends to form a complete current path.
[0071] The (4-SP)4Pb3Br prepared in Example 2 10 The detection performance of the single crystal X-ray detector constructed by 2H2O crystal was tested, and the results are as follows Figure 7 As shown, the test results show that (4-SP)4Pb3Br 10 The 2H2O single crystal X-ray detector exhibited excellent detection performance, with a device output of 278.1μC Gy in self-driven mode. -1 cm -2 High detection sensitivity; with the increase of bias voltage, the sensitivity also increases successively, and the sensitivity value reaches 10851.6μC Gy at 100V -1 cm -2 , which is the highest value among single-layer metal halide perovskite single crystal X-ray detection materials. At the same time, as shown in Figure 8, the detection limit in self-driven mode and 100V bias is as low as 17.9nGy s -1 and 368.3 nGy s -1, is commercial α-Se (5500nGy s -1 ) 307 times and 15 times.
[0072] The (4-SP)4Pb3Br prepared in Example 2 10 The stability of the single crystal X-ray detector constructed with 2H2O crystal was tested. Figure 9 As shown, the test results show that (4-SP)4Pb3Br 10 The dark current drift of the 2H2O single crystal X-ray detector at a bias voltage of 100V is as low as 2.1×10 -8 nAcm -1 s -1 V -1 , which can effectively inhibit ion migration.
[0073] Figure 10 (4-SP)4Pb3Br prepared in Example 2 10 The stability of the 2H2O crystal was tested under high X-ray irradiation doses. It can be seen that the detector can also operate stably for a long time under high X-ray irradiation doses.
[0074] Figure 11 (4-SP)4Pb3Br prepared in Example 2 10 Comparing the initial detection sensitivity of the 2H2O crystal with the sensitivity two months later, it can be seen that after two months without vacuum packaging, the detector's detection sensitivity under a 100V bias can still maintain more than 95% of its initial efficiency.
[0075] All of the above demonstrate that the detection device has excellent stability.
[0076] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by a person skilled in the art within the technical scope disclosed in the present invention should be included in the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be based on the scope of protection of the claims.
Claims
1. A highly stable sulfide polar metal halide perovskite crystal, characterized in that: Its chemical formula is (4-SP)4Pb3Br 10 2H2O, wherein 4-SP represents 4-aminothiophenol.
2. The highly stable sulfide polar metal halide perovskite crystal according to claim 1, characterized in that: The sulfide polar metal halide perovskite crystal belongs to the orthorhombic crystal system and has a space group of Aea2.
3. The highly stable sulfide polar metal halide perovskite crystal according to claim 1, characterized in that: The unit cell parameters of the sulfide polar metal halide perovskite crystal are: α=90°, β=90°, γ=90°, Z = 4, density is 2.842 g / cm 3 .
4. A method for preparing a highly stable sulfide polar metal halide perovskite crystal according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: mixing 4-aminothiophenol and lead acetate trihydrate, then adding an HBr aqueous solution, heating and stirring until the solution becomes a colorless clear solution; and performing a crystallization post-treatment on the obtained colorless clear solution to obtain a highly stable sulfide polar metal halide perovskite crystal.
5. The preparation method according to claim 4, characterized in that The specific operation steps of the crystallization post-treatment include: placing the obtained colorless clear solution in a high-temperature oven at a temperature of 120° C. while it is still hot, and slowly cooling the solution to room temperature by a slow cooling growth method at a cooling rate of 1° C. per day.
6. The preparation method according to claim 4 or 5, characterized in that The molar ratio of the 4-aminothiophenol to lead acetate trihydrate is 1.5:
1.
7. The preparation method according to claim 4 or 5, characterized in that The molar ratio of the lead acetate trihydrate to HBr in the HBr aqueous solution is 1:(20-35).
8. The preparation method according to claim 4 or 5, characterized in that The mass fraction of the HBr aqueous solution is 48%.
9. The preparation method according to claim 4 or 5, characterized in that The heating temperature is 80-120°C.
10. Use of the highly stable sulfide polar metal halide perovskite crystal according to any one of claims 1 to 3 in the preparation of an X-ray detector.
Citation Information
Patent Citations
Method for synthetizing high-stability metal halide perovskite / lead sulfide heterostructure nanocrystals
CN105602560A
Preparation method of two-dimensional perovskite polycrystalline slice X-ray detector and detector
CN117096214A
Organic-inorganic hybrid perovskite crystal and preparation method and application thereof
CN119020861A
Two-dimensional perovskite single crystal, preparation method thereof and X-ray detector
CN119507022A
Monolithic integration of hybrid perovskite single crystals with silicon for highly sensitive x-ray detectors
US20190162865A1
